Adults' Ability to Interpret Canine Body Language during a Dog–Child Interaction. (30th December 2016) - Demirbas, Yasemin Salgirli; Ozturk, Hakan; Emre, Bahri; Kockaya, Mustafa; Ozvardar, Tarkan; Scott, Alison
ABSTRACT: Child safety around dogs is an important issue since most dog bites involve small children. The supervision of children and dogs whilst they are together is therefore crucial. This study aimed to investigate the ability of adults to interpret canine body language and behavior during a child–dog interaction. An online survey about three selected videos, each showing small children interacting with dogs, was sent to four different groups of participants: dog owners with children, dog owners without children, non-dog owners with children, and non-dog owners without children. The dogs appearing in the videos were categorized as fearful/anxious and lacking in confidence by an expert panel. According to the answers given by 71 participants, people mostly classified the dogs as relaxed (68.4%) and confident (65.1%) during the dog–child interaction. Respondents reported the predominant behaviors of the dogs whilst they interacted with children as play (23.0%) and friendly behaviors (19.2%). Holistic cues (44.6%) were the most common cues referred to by respondents; these being cues that are qualitative assessments based on the dogs' behaviors, such as descriptions about the dogs' feelings, intentions, and judgments. Significant differences were found between dog owners and non-dog owners in describing the dogs' emotions in the videos. Participants without dogs were more successful than dog owners when classifying the emotional states of the dogs. These findings indicate that adults have difficulty in reading behavioral signs of anxiety and fear in dogs interacting with children. Moreover, it was shown that having experience with a dog without any theoretical knowledge of dog behavior may be a detriment to interpreting canine language. Therefore, the education of adults on dog behavior as well as on safe practices during child–dog interaction is important in the prevention of dog bites to children.